Can Russia Compete? - Desai, Raj M.; Goldberg, Itzhak (Washington, DC: Brookings Institution Press, 2017)
Russia has joined the club of rapidly growing economies, driven by rising prices for oil and gas. Russian authorities are concerned about sustaining this economic performance, however. Thus they have sought to diversify and broaden the basis for growth beyond the profitable natural resource sector and to build an economy that will be able to compete in the twenty-first century. This book presents the case that Russia’s neglected manufacturing sector is in need of human capital andpolicy reforms that will unleash its innovative potential. Can Russia Compete? quantifies and benchmarks the relative strengths and weaknesses of that sector, identifying opportunities to increase Russian productivity and competitiveness. Drawing on original survey data from Russian firms of all sizes, the authors formulate proposals that aim to enhance the innovative potential of Russian firms,upgrade the skills of their workforces, and develop a business-friendly climate with lower administrative costs and greater policy certainty. The original research and analysis of Raj Desai, Itzhak Goldberg, and their colleagues will be of use to anyone interested in the problems of building manufacturing competitiveness in a globally integrated economy. It will also be of interest to organizations planning to do business or invest in Russia.